Product/Service Systems Experiences – an International Survey of Swedish, Japanese, Italian and German Manufacturing Companies - Lindahl, M.; Sakao, T.; Sundin, E.; Shimomura, Y. (Cranfield University Press, 2009)
Product/Service Systems have recently grown in manufacturers’ interest. This paper presents an international survey of manufacturers from Sweden, Japan, Italy and Germany. The results show that customer connection and demands along with increased competition were main driving forces for product/service systems. Also, most product/service systems include physical products, maintenance and repairs. Staff working with product development, marketing and after sales were the major actors in product/service system development. As in traditional product sales, most product/service systems still have the ownership of physical products transferred to the customer/user. Physical products used in product/service systems are seldom adapted for product/service systems.
Organised by: Cranfield University
Keywords: PSS; IPSE; Service Engineering; Functional Sales; Remanufacturing